Determination of the absolute accuracy of UK chamber facilities used in measuring methane emissions from livestock. (April 2015) - Gardiner, T.D.; Coleman, M.D.; Innocenti, F.; Tompkins, J.; Connor, A.; Garnsworthy, P.C.; Moorby, J.M.; Reynolds, C.K.; Waterhouse, A.; Wills, D.
Highlights: Agriculture is estimated to contribute 50% of European emissions of methane. Respiration chambers are the primary source of agricultural methane emission data. A unique exercise has been conducted to validate 6 different UK chamber facilities. This established the uncertainty and provided traceability for the measurements. The overall uncertainty across the facilities has dropped from 25.7% to 2.1%. Abstract: Respiration chambers are one of the primary sources of data on methane emissions from livestock. This paper describes the results from a coordinated set of chamber validation experiments which establishes the absolute accuracy of the methane emission rates measured by the chambers, and for the first time provides metrological traceability to international standards, assesses the impact of both analyser and chamber response times on measurement uncertainty and establishes direct comparability between measurements made across different facilities with a wide range of chamber designs. As a result of the validation exercise the estimated combined uncertainty associated with the overall capability across all facilities reduced from 25.7% ( k = 2, 95% confidence) before the validation to 2.1% ( k = 2, 95% confidence) when the validation results are applied to the facilities' data.